2002
DOI: 10.1212/wnl.58.1.79
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiologic study of 203 sibling pairs with Parkinson’s disease

Abstract: The greater similarity for age at onset than for year of onset in sibling pairs with PD, together with increased risk for biological relatives over spouses of cases, supports a genetic component for PD. Risk to siblings in this series is increased over that seen in random series of PD cases; however, patients in this sample have similar ages at onset and sex distribution as seen for PD generally. These analyses suggest that factors influencing penetrance are critical to the understanding of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 47 publications
6
42
2
Order By: Relevance
“…When restricting the analyses to head trauma that occurred 10 years or more before the diagnosis of PD, the association remained [624]. A study of sibling pairs in which both had a PD diagnosis reported that the sibling with a previous head trauma had earlier age at onset (p=0.03) than the sibling without head trauma [625].…”
Section: Head Traumamentioning
confidence: 99%
“…When restricting the analyses to head trauma that occurred 10 years or more before the diagnosis of PD, the association remained [624]. A study of sibling pairs in which both had a PD diagnosis reported that the sibling with a previous head trauma had earlier age at onset (p=0.03) than the sibling without head trauma [625].…”
Section: Head Traumamentioning
confidence: 99%
“…As in AD, there appears to be an age-dependent dichotomy: the majority of individuals with an early or even juvenile onset show typical Mendelian inheritance. However, unlike in AD, these cases show a predominantly autosomal-recessive mode of inheritance, and there is an ongoing debate as to whether genetic factors play any substantial role in contributing to disease risk in cases with onset beyond approximately 50 years (29)(30)(31).…”
Section: Parkinson Diseasementioning
confidence: 99%
“…Neurologists from the participating sites examined and confirmed the diagnosis of each PD affected individual included in the study as previously described (Maher et al 2002). Diagnostic criteria for PD were based on the United Kingdom PD Society Brain Bank Criteria (Gibb and Lees 1988) with slight modification.…”
Section: Subjectsmentioning
confidence: 99%